1992
DOI: 10.1159/000111660
|View full text |Cite
|
Sign up to set email alerts
|

Raphe Grafts in the Hippocampus, But Not in the Entorhinal Cortex, Reverse Hippocampal Hyperexcitability of Serotonin-Depleted Rats and Restore Their Responsiveness to Fenfluramine

Abstract: We compared the effects of embryonic raphe grafted into either the hippocampus or the entorhinal cortex, on the responsiveness of dentate granule cells to stimulation of the perforant path. Raphe grafts in the hippocampus reversed the hyperexcitability of granule cells, resulting from depletion of the serotonergic innervation. Such grafts also restored the responsiveness of the granule cells to application of a serotonin releasing drug, fenfluramine (FFA). In contrast, hyperexcitability was not reversed when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Raphe grafts in the hippocampus reduced the behavioural impairment. When located in the hypothalamus such grafts had no effect on spatial learning, as was found with raphe grafts in the entorhinal cortex (Richter-Levin and Segal, 1992;Richter-Levin et a/., 1993). In addition, we now found that the 5,7-DHT lesions affected the forebrain serotonergic fibres but had a much smaller effect on the midbrain serotonergic innervation.…”
Section: Discussionsupporting
confidence: 68%
“…Raphe grafts in the hippocampus reduced the behavioural impairment. When located in the hypothalamus such grafts had no effect on spatial learning, as was found with raphe grafts in the entorhinal cortex (Richter-Levin and Segal, 1992;Richter-Levin et a/., 1993). In addition, we now found that the 5,7-DHT lesions affected the forebrain serotonergic fibres but had a much smaller effect on the midbrain serotonergic innervation.…”
Section: Discussionsupporting
confidence: 68%
“…The finding that mEPSCs are not affected, neither in frequency nor in amplitude, could be in line with the following scenario: 5-HT could induce a hyperpolarization of the presynaptic pyramidal cell, mediated by the opening of GIRK channels by 5-HT 1A receptor activation ( Andrade and Nicoll 1987 ; Segal et al 1989 ; Schmitz et al 1995 ). This would diminish the frequency of sEPSCs because of a decrease in the number of spontaneous spikes as has been shown in vivo ( Richter-Levin and Segal 1992 ). This possibility seems to be unlikely because application of a GIRK-channel blocker could not prevent the reduction of excitatory synaptic transmission onto O-LM interneurons by 5-HT.…”
Section: Discussionmentioning
confidence: 85%
“…These data suggest that both 5‐HT 1A and NMDA receptor activation may regulate neurogenesis throughout changes in activity of mature granule cells, via common or independent pathways. In the present study, transplanted foetal 5‐HT neurons may also affect neurogenesis via the same mechanism, because electrophysiological studies have demonstrated that raphe cells grafted into the hippocampus can prevent the 5‐HT‐depletion‐induced hyperexcitability of the dentate gyrus (Richter‐Levin & Segal 1992). Thus, although serotonergic denervation may have affected granule cell proliferation via changing overall electrical activity in the brain, the present transplantation study supports the view that 5‐HT may act locally on adult neurogenesis in the hippocampal formation.…”
Section: Discussionmentioning
confidence: 88%
“…1989, 1991). Furthermore, raphe grafts can reverse the 5‐HT‐depletion‐induced hyperexcitability of granule cells to perforant path stimulation (Richter‐Levin & Segal 1992) and ameliorate spatial memory impairments caused by combined lesions of 5‐HT and cholinergic neurons (Nilsson et al . 1990; Richter‐Levin et al .…”
Section: Introductionmentioning
confidence: 99%